- #1

- 26

- 0

[tex]\Gamma^{j}_{cd}=\Gamma^{j}_{cd}[/tex]

[tex]g^{cd}\Gamma^{j}_{cd}=g^{cd}\Gamma^{j}_{cd}[/tex]

[tex]\frac{1}{2}g^{cd}g^{jm}\left(g_{md,c}+g_{mc,d}-g_{cd,m}\right)=\frac{1}{2}g^{cd}g^{jm}\left(g_{md,c}+g_{mc,d}-g_{cd,m}\right)[/tex]

[tex]\frac{1}{2}g^{cd}g^{jm}\left(g_{md,c}+g_{mc,d}-g_{cd,m}\right)=\frac{1}{2}g^{ab}g^{jm}\left(g_{mb,a}+g_{ma,b}-g_{ab,m}\right)[/tex]

[tex]\frac{1}{2}g^{jm}\left(g_{md,c}+g_{mc,d}-g_{cd,m}\right)=\frac{1}{2}g_{cd}g^{ab}g^{jm}\left(g_{mb,a}+g_{ma,b}-g_{ab,m}\right)[/tex]

[tex]\Gamma^{j}_{cd}=g_{cd}g^{ab}\Gamma^{j}_{ab}[/tex]